1998
DOI: 10.1007/s005350050161
|View full text |Cite
|
Sign up to set email alerts
|

Unusual gastric polyp showing submucosal proliferation of glands: Case report and literature review

Abstract: We report an unusual pedunculated polyp in the stomach in a 41-year-old woman. She was hospitalized because of epigastric discomfort. Endoscopy revealed a polyp with a long stalk in the fundus of the stomach. The polypectomyzed polyp measured 23 x 18 x 9 mm and was characterized by submucosal proliferation of glands and cystic dilatation. The surface of the polyp was covered with gastric mucosa of fundic or pyloric gland type. The glandular structures consisted of various types of lining cells, including pylor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 13 publications
1
37
1
Order By: Relevance
“…To date, 35 cases of gastric IHP, including the present case, have been described in the English-language literature. Although the pathogenesis of IHP is not understood, studies suggest that inflammation and subsequent healing may promote the epithelial displacement 4,5. In our patient, the connection between the inflamed overlying mucosa and the hyperplastic component, and the presence of the slit-shaped cavity in the center suggested that repeated mucosal inflammation caused a break in the muscularis mucosae, which permitted the downward herniation and submucosal trapping of mucosal glands.…”
Section: Discussionmentioning
confidence: 61%
“…To date, 35 cases of gastric IHP, including the present case, have been described in the English-language literature. Although the pathogenesis of IHP is not understood, studies suggest that inflammation and subsequent healing may promote the epithelial displacement 4,5. In our patient, the connection between the inflamed overlying mucosa and the hyperplastic component, and the presence of the slit-shaped cavity in the center suggested that repeated mucosal inflammation caused a break in the muscularis mucosae, which permitted the downward herniation and submucosal trapping of mucosal glands.…”
Section: Discussionmentioning
confidence: 61%
“…GHIPs are characterized pathologically by cystic, dilated, hypertrophic pseudopyloric gland proliferation and by smooth-muscle fibers located in the submucosal layer, with branching from the proliferation of smooth-muscle bundles. The main lesion in GHIP is located in the submucosa or within the muscularis mucosae 3.…”
Section: Discussionmentioning
confidence: 99%
“…GHPs are pathologically defined by cystic dilated hypertrophic pseudo-pylorus gland proliferation and smooth muscle located in the submucosal layer with branching from the proliferation of smooth muscle bundles [7] . Although Peutz-Jeghers syndrome, juvenile polyposis and Cowden disease are hereditary, it is rare to encounter 2 cases of monostotic and asymptomatic gastric hamartomas [8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%